BIMBINGAN ISLAM BAGI KETEGANTUNGAN NAZA (Narkotika, Alkohol, dan Zat Adiktif Lainnya) - Lutfi, M.; Rais, Muhamad Fauzi (Dakwah: Jurnal Kajian Dakwah dan Kemasyarakatan, 2024)
Abuse of "NAZA" (Narcotics, Alcohol and other Addictive Substances) or "DRUGS" (Narcotics, Drugs and Psychotropic Substances) is an "opium" that makes people dependent on it, is "a condition that can be conceptualized as a "mental disorder" . Where naza abuse (sufferers) are no longer able to function normally in society, and show "maladaptive" behavior (deviant behavior)".  Thus, victims of naza abuse and drug (opium) dependence have had their mental health disturbed, because they have consumed naza/drugs outside the requirements for medical treatment (therapy). As a result of these mental disorders, sufferers are unable to adapt and interact properly with family, peers and the surrounding environment. Therefore, continuous guidance assistance is needed for victims using a religious approach, namely awakening and reviving their "consciousness of faith" (spiritual) through spiritual (mental or psychological) touches with "soul/spiritual purification" (tazkiyat an -nafs), repentance, dhikr, and muhasabah and ask for guidance and healing from God the Almighty Creator, Allah SWT.